Coupled Coordination of Land and Water Use Efficiency in Huaihe River Basin and Its Spatial and Temporal Divergence - He Gang; Zhang Shiyu; Bao Keyu; Yang Xia; Hou Xiaoyu (Shuitu baochi tongbao)
[Objective] The utilization efficiency of land and water resources in the Huaihe River basin was evaluated to clarify the degree of coupling and coordination between the two and their spatial differentiation characteristics, in order to provide a theoretical reference for improving the utilization efficiency of land and water resources and promoting the benign and coordinated development of land and water resources in the basin. [Methods] The Super-SBM model was used to measure the land and water resource utilization efficiencies of 30 cities in the Huaihe River basin. The coupling coordination degree model was constructed to discuss the coordinated development of the two. The standard deviation ellipse and the Dagum Gini coefficient method were used to analyze the spatial deviation degree and spatial differentiation source of the coupled coordination degree. [Results] ① During the study period, the utilization efficiency of land and water resources in the Huaihe River basin showed a fluctuating upward trend, and the spatial heterogeneity was significant. ② From 2011 to 2014, the degree of coupling and coordination between the two factors was in the barely coordinated stage. From 2015 to 2020, the degree of coupling and coordination was basically in the primary coordination and intermediate coordination stage, both of which were dominated by the lag of water resource utilization efficiency. A spatial pattern of “higher in the east and west, and lower in the middle” was gradually presented. ③ The coupling and coordination degree of land and water resource utilization efficiency in the northwest and southeast cities of the Huaihe River basin increased rapidly, and there was a phenomenon of strong and weak alternation. ④ The overall difference of the coupling coordination degree between the two showed a downward trend, and the spatial differentiation mainly came from the hypervariable density, followed by regional differentiation. [Conclusion] The utilization efficiencies of urban land resources and water resources in the Huaihe River basin were not high, and the coupling coordination degree was also low. Cities should strengthen the efficient and intensive use of water and land resources, improve the coupling coordination degree between the two, and provide a decision-making basis for the implementation of differentiated resource development strategies in various regions.